Urinary tract infections, risk factors and antimicrobial resistance patterns in heart failure patients on sodium-glucose transporter 2 inhibitors: Evidence from Jakaya Kikwete Cardiac Institute in Tanzania - Julieth Kaaya; Martine A. Manguzu; Deus Buma; Hamu Mlyuka; Samwel Rweyemamu; Albert Ntukula; Helfrid B. Ilomo; Elias Bukundi; Raphael Sangeda; Ritah F. Mutagonda (PLoS ONE, 2026)
Background Sodium-glucose co-transporter 2 (SGLT2) inhibitors such as dapagliflozin and empagliflozin are increasingly used in heart failure (HF) management due to their cardiovascular benefits. However, glycosuria induced by SGLT2 inhibition may increase the risk of urinary tract infections (UTIs). Limited data exist on UTI burden among HF patients on SGLT2 inhibitors in low-resource settings. Objective This study aimed to determine the prevalence of UTIs, associated factors, and antimicrobial susceptibility patterns of uropathogens in HF patients receiving SGLT2 inhibitors at the Jakaya Kikwete Cardiac Institute (JKCI) in Tanzania. Methods A hospital-based cross-sectional study was conducted from March to June 2024 among HF patients aged ≥18 years on SGLT2 inhibitors. Data was collected using structured questionnaires and medical records. Midstream clean-catch urine samples were collected in sterile containers and processed using semi-quantitative urine culture on CLED and blood agar and subjected to antimicrobial susceptibility testing using the Kirby-Bauer disk diffusion method per CLSI M100 (2024) guidelines. Descriptive statistics and modified Poisson regression were used for analysis. Results Out of 138 urine samples processed, 22 (15.9%) showed significant growth. The most common uropathogen was Escherichia coli (50.0%), followed by Klebsiella pneumoniae (13.6%), Pseudomonas aeruginosa (9.1%), and Candida spp. (9.1%). Significant risk factors for UTI included age > 60 years (aPR 3.77; 95% CI: 1.42–10.01), female sex (aPR 2.92; 95% CI: 1.19–7.15), and SGLT2 inhibitor use ≥ 4 months (aPR 3.19; 95% CI: 1.70–5.96). High resistance was observed among bacterial isolates against ampicillin (100%), tetracycline (69.2%), and ceftazidime (53.8%), whereas high susceptibility was noted against nitrofurantoin (84.6%) and meropenem (100%). Conclusion UTIs are common among HF patients on SGLT2 inhibitors, with E. coli as the predominant pathogen and a concerning resistance to commonly used antibiotics. These findings underscore the need for routine urine culture and sensitivity testing to guide appropriate therapy and promote antimicrobial stewardship, particularly in resource-constrained settings.